Variations on the chemical compositions of chestnut fruits collected at different locations - Nezahat Turfan; Ferhat Kara; Mehtap Alay (BioResources, 2024)
Chestnut is an essential food source in many countries. Nutritional quality and potential health benefits of Anatolian chestnut trees (Castanea sativa Mill.) have led to increased concern and interest in chestnut production. However, knowledge of the factors that influence the chemical content of chestnut fruits still needs to be improved. Thus, the chemical compositions were evaluated for Anatolian chestnut fruits collected at 14 different locations in northern Türkiye, which is one of the biggest chestnut producers in the world. The effects of latitude, longitude, altitude, aspect, mean annual temperature (°C) (TMA), and mean annual precipitation (mm) (PMA) of the study locations on the chemical compositions of chestnut fruits were monitored. The effects of these parameters on several chestnut characteristics were examined using a mixed-effects multiple regression model. Latitude, longitude, TMA, and PMA were correlated with the mean concentrations of sucrose, free amino acid, glycine betaine, nitrogen (N) (%), and total carbon (C) (%) of the chestnut samples. The moisture content of the fruits was affected by longitude. The antioxidant and mineral content of the chestnut samples also varied by location. These findings may be helpful in site selection, production, and conservation of chestnut cultivars.
Keywords: castanea sativa; chemical contents; environment; TP248.13-248.65; cultivar; Biotechnology